Pola asuh, pola makan, asupan zat gizi dan hubungannya dengan status gizi anak balita masyarakat Suku Nuaulu di Kecamatan Amahai Kabupaten Maluku Tengah Provinsi Maluku - Muhamad Asrar; Hamam Hadi; Dradjat Boediman (Jurnal Gizi Klinik Indonesia, 2009)
Background: Nomadic life of Nuaulu Tribe results in rearing pattern, eating pattern, and food consumption which affect their nutritional status.Objective: To identify the relationship between rearing pattern, eating pattern, nutrient intake, and nutritional status of under-fives of Nuaulu tribal community at Subdistrict of Amahai, District of Maluku Tengah, Province of Maluku.Method: This was an observational analytical study with cross sectional design. Subjects of the study were 68 under-fives of age 12 to 60 months from Nuaulu Tribal community at Sub district of Amahai. Data of rearing pattern were obtained from interviewing using questionnaire, data of eating pattern from food frequency questionnaire, data of nutrient intake from recall 24 hours, and data of nutritional status from anthropometric measurement. Data analysis used bivariable with chi-square, multivariate with double logistic regression.Results: Most samples had low category of rearing pattern (77.9%) and eating pattern (66.2%); whereas samples intake of energy and protein belonged to adequate category, that were 73.6% and 72.0%, respectively. Nutritional status based on index of weight/age of 20.6% samples belonged to undernourished category and 51.5% samples belonged to stunted category based on index of length/age. There were no significant relationship between rearing pattern and nutritional status based on index of weight/length and weight/age (p > 0.05), but there was relationship between them based on index of length/age (p < 0.05). Eating pattern and nutritional status based on index of weight/length and weight/age had no relationship (p > 0.05), but between eating pattern and nutritional status based on index of length/age had relationship (p < 0,05). There was significant relationship between energy intake and nutritional status based on index of weight/age and length/age (p < 0.05), but there was not based on weight/length index (p > 0.05). There was significant relationship between protein intake and nutritional status based on index of weight/age and length/age (p < 0.05); however the relationship was insignificant based on index of weight/length.Conclusion: There was significant relationship between rearing pattern and nutritional status based on index of length/age and so was between eating pattern and nutritional status based index of length/age. Energy, protein intake and nutritional status based on index of weight/age and length/age also had significant relationship.